The role of private capital flows and financial deepening in the economic growth of South Africa - Karimatsenga, Sharon (Graduate School of Business (GSB), 2018)
This research examines the role of Private Capital Flows (PCF) and Financial Deepening in the economic growth of South Africa. Using secondary data obtained from the South African Reserve Bank and the World Bank online databases for the period 1990 to 2015, we examine the relationship between these three variables using the Autoregressive Distributed Lag (ARDL) bounds testing procedure. The causal relationship between the variables is further investigated using the Granger Causality test. Where previous studies mainly focus on investigating the relationship between capital flows and economic growth; and that of financial deepening and economic growth in South Africa independently; this study looks at the interrelationship between these three variables. Contrary to our expectations, the findings from the research suggest that there is no significant long run relationship between these variables in South Africa; however we found significant unidirectional short run causal relationships between the variables. The study established that in the short run, economic growth granger causes private capital flows; financial deepening granger causes private capital flows and that economic growth granger causes financial deepening. These findings imply that putting in place policies that encourage economic growth will lead to improvements in both PCF and financial deepening in the short run. In turn, improvements in financial deepening will also foster improvements in PCF in the short run. The results, policy implications, and future research are discussed.